PENINGKATAN KEMAMPUAN PROFESIONAL LULUSAN SMK KELOMPOK PARIWISATA MELALUI UNIT PRODUKSI BOGA - Marwanti Marwanti (Universitas Negeri Yogyakarta, 1999)
Abstract This purpose of this action research is to improve the professiona ability of the graduates of the Tourism Group of Vocational Secondary Schools. Actions are conducted through the activity in the culinary production unit of a vocational ssecondary school. The research was carried out in one cycle consisted of reconnaissance, planning, and combination of observation and reflection. The subjects of this research are 32 students who are majoring in Culinary at the Vocational Secondary School (SMK)No 6 of Yogyakarta. The treatment is of the form of orders for menu of the same level of difficulties given to each student. Variables observed are working capability, working skill, responsibility, working speed, working tidiness, and personal appearance. Data were collected by observation and analyzed by descriptive method. The result shows that the actions improve most of the students’ abilities. It indicates that culinary course in the form of assignment requiring individual responsibility of each studentis more effective than that in the form of group assignment. It can be concluded that culinary practices by individual student increase the student’s ability more intensively than group practices. Keywords: action research, culinary production unit.